Development of ground station communication system for an advanced nano-satellite VELOX II - Wee, Doreen Zhen Hua (2014)
Following VELOX-I, the first nano-satellite project of NTU Undergraduate Satellite Program, VELOX-II is the next nano-satellite project which is now also in the midst of development and prototyping stage.